Boosting Of Women Education in Ed- Tech Sector Digital Economy Era - Khalsiah (LPPM Universitas Malikussaleh, 2022)
Knowledge and ICT will have a very dominant impact in the future. The role of women and the quality of the education sector will place women in the position of enhancing the quality of science and technology and the future generations of women in world civilization. Based on the substance of the theme, this study examines: How women are classified and explained in the digital economy era and what factors support and hinder women's empowerment in the digital economy era. The research method uses descriptive. The study results show that the linkage of women's empowerment in science and technology can improve the quality of welfare in a country. Digital technology is synonymous with gender labeling than science and technology, making men's position more domain. The effect that causes women to be far behind in technology Women needs to improve the quality of education and master various technology platforms to play a role in multiple sectors, both digital marketing and the development sector and decision-makers. The presence of numerous technologies in education (ED-Tech) at the university level; will boost the learning process for women.